Advances in Production Research Proceedings of the 8th Congress of the German Academic Association for Production Technology (WGP), Aachen, November 19-20, 2018 - Schmitt, Robert; Schuh, Günther; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
The papers in this volume present recent and highly relevant topics in the fields of production research as 3D printing, additive manufacturing processes, agile product development, change dynamics in companies, configurable material systems, data analysis in process optimization, future technologies with high potential in value creation, global production, learning production systems, production of the future, organization of assemblies, resource efficiency in production, robotics in assembly, and technology trends in machine tools. Researchers and practitioners in the field of mechanical engineering and production technology will benefit from this content.
Machines and data of the future -- Assembly and production systems -- Material and manufacturing systems -- Future production -- Product development and resource efficiency.
Keywords: Manufactures; Machines, Tools, Processes